1988
DOI: 10.1182/blood.v71.5.1304.bloodjournal7151304
|View full text |Cite
|
Sign up to set email alerts
|

Serum soluble IL-2 receptor as a tumor marker in patients with hairy cell leukemia

Abstract: Activated T cells synthesize and express a cell membrane-bound receptor for interleukin-2 (IL-2) and have recently been shown to secrete a soluble form of the same receptor. Hairy cell leukemia is a chronic disorder caused by expansion of a clonal population of an unusual mononuclear cell of B cell origin. These cells have previously been shown to express an IL-2 receptor on the cell membrane. The sera of 26 patients with hairy cell leukemia were examined for the presence of a soluble IL-2 receptor before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…It is well known that increased levels of the soluble sIL-2Ra in biological fluids correlate with increased T-and B-cell activation and immune system activation (Waldmann, 1986). Many studies in the literature suggest a correlation between elevated sIL-2Ra and disorders that are associated with cellular immune activation (Semenzato et al, 1987;Steis et al, 1988). Furthermore, Motoi et al (1989) demonstrated that serum sIL-2Ra levels are a useful clinical indicator of the leukaemic cell burden in vivo, as leukaemic cells from CML patients with blastic crisis expressed and released IL-2 receptor (Tac antigen) (Motoi et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that increased levels of the soluble sIL-2Ra in biological fluids correlate with increased T-and B-cell activation and immune system activation (Waldmann, 1986). Many studies in the literature suggest a correlation between elevated sIL-2Ra and disorders that are associated with cellular immune activation (Semenzato et al, 1987;Steis et al, 1988). Furthermore, Motoi et al (1989) demonstrated that serum sIL-2Ra levels are a useful clinical indicator of the leukaemic cell burden in vivo, as leukaemic cells from CML patients with blastic crisis expressed and released IL-2 receptor (Tac antigen) (Motoi et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The serum level of sIL-2K in HCL at diagnosis is extremely high (Greene et al, 1986;Chilosi et al, 1987) and can be regarded as a useful diagnostic marker in the context of the clinical picture of the disease (Pizzolo et al, 1987a). Interestingly, in HCL patients successfully treated with alpha interferon (alpha-IFN) a decrease in serum sIL-2R level parallels the improvement in haematologic parameters and the reduction of splenomegaly and of BM HC infiltration (Chilosi et al 1987;Steis et al, 1988).…”
mentioning
confidence: 99%
“…This antigen, which is characteristic of activated T cells, has also been found on special categories of activated B cells (1,32). In HCL this antigen is especially strongly expressed and it can even be secreted (33,34). B-CLL does not normally express IL2-R but can be induced to do so with phorbol ester or other inducers (35).…”
Section: Discussionmentioning
confidence: 99%